Marketing to UK retailers: understanding the nature of UK retail buying of textiles and clothing - Vinhas da Silva, R.; Davies, G.; Naude, P. (Journal of Fashion Marketing and Management, 2000)
This paper examines the likely influences on the sourcing of textiles by UK retail buyers. It reports the results of secondary data analyses on the retail market and primary data from personal interviews with 102 textile buyers. The main influence on the British market from changes in international agreements will be a greater opportunity to source from low-cost markets. This could negatively affect traditional sources such as Italy and Portugal. The structure of the UK market is analysed to provide a basis for the selection of interviewees. Buyers who were interviewed tended to fall into two groups, younger but well qualified and older, less well qualified but more experienced. The younger group included more females. They tended to refer important decisions to others, although this correlated more with experience than with gender. Conclusions are drawn on the implications of the study for textile marketers, particularly those from other EU countries. By enhancing their understanding of the structure of the UK retail sector, suppliers are able to devise strategies that take into account the specific nature of distribution of textiles and clothing in the UK, and consequently increase their ability to compete in this changing market.